Dry sliding wear behaviour of A390 hypereutectic (Al–Si) alloy - Riyadh A., Al-Samarai; Haftirman, Idrus; Khairel Rafezi, Ahmad, Dr.; Yarub, Al-Douri (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.